Desenvolvimento de aplicativo para cálculo das emissões de gases de efeito estufa para a cultura da cana-de-açúcar - Pereira, Lucas Gabriel dos Santos (Universidade Federal de São Carlos, 2025)
Global climate change, driven by increasing atmospheric concentrations of greenhouse gases (GHG), places the agricultural sector at the center of mitigation debates, both due to its contribution to emissions and its potential for carbon sequestration through conservation management practices. In Brazil, sugarcane cultivation stands out for its high economic and energy relevance, positioning it as a strategic sector in the transition toward a low-carbon economy. However, despite the availability of consolidated methodologies for GHG inventories, such as IPCC guidelines and widely recognized tools, their practical application among rural producers remains limited due to high technical complexity, elevated costs, and low accessibility. This study is based on the hypothesis that these limitations hinder the democratization of access to environmental information and restrict producers’ participation in the carbon market. In this context, the objective of this study was to conceptually develop and prototype a mobile application specifically designed for sugarcane cultivation within the Brazilian context, using a no-code approach and generative artificial intelligence resources as a development support tool, while the calculation logic itself is entirely grounded in consolidated scientific methodologies. The application estimates Scope 1 and Scope 2 emissions, prioritizing data that are easily obtainable by producers. As a result, a functional prototype with a simplified interface was developed, capable of estimating emissions in CO₂ equivalent, identifying critical emission sources, and supporting environmental management in sugarcane production systems, thereby contributing to bridging the gap between science, technology, and productive reality in the sugar-energy sector.
Development of an application for calculating greenhouse gas emissions for sugarcane cultivation
Keywords: Cana-de-açúcar; Inventário de GEE; Pegada de carbono; Agricultura de baixo carbono; Inteligência artificial; Sugarcane; GHG inventory; Carbon footprint; Low-carbon agriculture; Artificial intelligence; CIENCIAS AGRARIAS::AGRONOMIA; 13. Ação contra a Mudança Global do Clima